Typology of precedent religious phenomena represented in the artistic prose by Vasyl Shkliar (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
Despite the considerable interest of scientists in the problem of the representation of precedent phenomena in artistic speech (L. Baranska (M. Matios), A. Berestova (V. Baziv, A. Kokotyukha, V. Lys, M. Matios), T. Kalchenko (I. Rymaruk, V. Herasymyuk), J. Koloiz (V. Shkliar), L. Olefirenko (V. Stus), M. Skab (O. Honchar), H. Siuta (Ukrainian poetic language of the 20th century), M. Filon (T. Shevchenko), O. Telezhkina (A. Andrukhovych, V. Bazylevsky, S. Sapelyak), O. Tsyperdyuk (V. Herasymyuk)), the typological characteristics of precedent religious phenomena in the prose works by Vasyl Shkliar have not been examined and analyzed in details yet. This fact actualizes the need to study precedent phenomena in the artistic language of the writer. The purpose of the article is to identify and characterize the typological features of precedent religious phenomena represented in the novels by V. Shkliar. Observations on the chosen illustrative material have showed that the writer actively uses precedent religious phenomena in all selected for analysis artistic works, although they differ in genre: “Nikub (Blood of the Bitch)” – a mystical detective, “Nostalgia” and “Shadow owl” – social psychological novels, “Marusya” – ahistorical novel.The results of the analysis of the illustrative material testify to the fact that by the level of precedentityone can distinguish nationally precedent phenomena and sociallyprecedent ones, the latter ones are of the religious origin;by the form of verbalization one can mark out verbal (precedent religious names (theonyms, angelonyms, demonyms, biblicalmythotoponyms, iconyms, biblionyms (clergionyms, deprecationyms), ecclesionyms, heortonyms) and precedent religious expressions) and verbalized (precedent religious texts and precedent religious situations) religious phenomena. The chosen precedent religious units are used in the “canonical form”, that is they have not undergone transformation, and are used mainly as unmarked fragments of texts of religious content, which, acting as an organic component of the narration, are elements of the language game and serve as the organizational principle in the narrative.
Keywords: precedent religious phenomenon; precedent level; form of verbalization; transformation